Nas trilhas das experiências formativas da docência no programa residência pedagógica: relação preceptoras e licenciandas de pedagogia - Oliveira, Mirian Gordiano Lima (2022)
This research has as its object the formative experiences of preceptors of the Pedagogical Residency Program with undergraduates in pedagogy at UEFS. It addresses the trajectory of initial training that takes place in the daily life of schools, in the dialogue between the university and the basic school, through the UEFS Pedagogical Residency Program. Thus, the objective of the research is to understand the process of training basic education teachers, preceptors of the UEFS PRP. Based on this premise, the text is organized around three central ideas: the formative path of a trainer, the experience of everyday school life and the principles of formative horizontality; the history of the Pedagogical Residency Program; state of the art and, finally, the methodological course of a formative nature, woven by the teachers' narratives, inspired by the (auto)biographical method, having the narrative interview as a device for collecting information. The work is anchored in authors such as Nóvoa (1995, 1999, 2009), Gatti (2019), Larrosa (2002), Silva (2020), Josso (2020), Rios (2020) and others who contribute through their studies and experiences. developed in the process of teacher training. The research seeks to highlight the formative experiences of the preceptors in the way in which the relationships between the preceptors and the residents occur in the context of practices in the school routine and their role in the initial training of future teachers. the importance of theory at the time of its practice in the classroom, many emphasize that learning becomes significant when they are exercising the teaching profession. The research allowed us to conclude that the undergraduates value their insertion in the daily life of the school, as a way of understanding the fabric of teaching practice. Many confirm the idea that they produce a more significant learning experience in becoming a teacher through their experience in the teaching profession. Finally, it is concluded that educational praxis is what makes sense for the teacher who is teaching and together with the students learning, through reflection and criticality built through dialogue and in the collective.